INTEGRATION OF NEW PUBLIC GOVERNANCE AND LOCAL WISDOM IN PUBLIC SERVICES AT THE SUB-DISTRICT LEVEL: A CASE STUDY OF MUSI RAWAS REGENCY - Iman, Maidi Muhammad; Alfitri, Alfitri; Thamrin, Muhammad Husni; Alamsyah, Alamsyah (Natapraja, 2025)
This study examines public service governance at the sub-district level in Musi Rawas Regency, focusing on the integration of local wisdom and the principles of New Public Governance (NPG). The research highlights the importance of collaboration between government agencies, vertical institutions, and the community in improving service efficiency and responsiveness. Using a descriptive qualitative approach, the study identifies key elements of effective public service governance, including collaboration, flexibility, risk management, and innovation. The research aims to analyze how local wisdom can play a role in addressing contemporary challenges in public service, such as transparency and accountability. The integration of local wisdom is deemed capable of building trust and fostering active participation, particularly through personalized approaches that respect cultural values and the implementation of decentralized services. The study also emphasizes the importance of technology and policy frameworks in ensuring the sustainability of service innovations, including direct engagement with rural communities. The research method employs a descriptive qualitative approach, utilizing data collection techniques such as Focus Group Discussions (FGD), interviews, documentation, and observation, involving 20 key informants. The findings reveal that the combination of NPG principles with local wisdom can create a governance model that is not only efficient and transparent but also responsive to the values and needs of local communities. This integrated approach indirectly strengthens trust, accountability, and inclusiveness in public services while offering a model that can be applied in other regions facing similar challenges.